Advancing okra (Abelmoschus esculentus L. Moench) breeding to unlock inherent multi-stress resistance for efficiency and sustainability in agriculture - Mangena, Phetole; Gerrano, Abe Shegro; Truter, Mariette; Molatudi, Lucy; Gumede, Mbali Thembi; Khoza, Lindiwe; Masemola, Milcah; Nyathi, Melvin; Moalafi, Abueng (Frontiers in Plant Science, 2026)
Drought, pests and diseases constitute significant threats to food security, affecting crop growth and development, yield, grain quality, and causing a myriad of adverse physiological and biological effects in okra (Abelmoschus esculentus L. Moench) and many other crops. In 2024, the global okra production recorded approximately 11.23 million tons, with India leading the charts, accounting for over 70% of the world production due to environmental constraints. However, significant breeding advancements are being explored in mitigating the effects of biotic and abiotic stresses through the development of stress resilient varieties. Okra breeding for crop diversification face unique challenges characterized by genetic bottlenecks, complex trait inheritances, long breeding cycles and lack of confirmed inherent stress-resistant genes required for multi-stress tolerance. Emerging reports point to progressing breeding through modern techniques like marker-assisted selection (MAS) and genetic modification to develop varieties resistant to drought, pests and diseases. Therefore, this review outlines okra’s potential resistance to living and non-living stress factors, defines genes and mechanisms for possible effective mitigation, and challenges in conferring gene-mediated resistance. We propose efficient breeding strategies further required to enhance growth and productivity of okra, while guaranteeing a sustainably enhanced crop value chain under both favorable and unfavorable climate and environmental conditions.